Protection of Alcohol Dehydrogenase against Freeze–Thaw Stress by Ice-Binding Proteins Is Proportional to Their Ice Recrystallization Inhibition Property - Young Hoon Lee; Kitae Kim; Jun Hyuck Lee; Hak Jun Kim (Marine Drugs, 2020)
Ice-binding proteins (IBPs) have ice recrystallization inhibition (IRI) activity. IRI property has been extensively utilized for the cryopreservation of different types of cells and tissues. Recent reports demonstrated that IRI can also play a significant role in protecting proteins from freezing damage during freeze–thaw cycles. In this study, we hypothesized that the protective capability of IBPs on proteins against freeze–thaw damage is proportional to their IRI activity. Hence we used two IBPs: one with higher IRI activity (LeIBP) and the other with lower activity (FfIBP). Yeast alcohol dehydrogenase (ADH) was used as a freeze-labile model protein. IBPs and ADH were mixed, frozen at −20 °C, and thawed repeatedly. The structure of ADH was assessed using fluorescence emission spectra probed by 1-anilinonaphthalene-8-sulfonate over the repeated freeze–thaw cycles. The activity was monitored at 340 nm spectrophotometrically. Fluorescence data and activity clearly indicated that ADH without IBP was freeze-labile. However, ADH maintained about 70% residual activity after five repeated cycles at a minimal concentration of 0.1 mg mL-1 of high IRI-active LeIBP, but only 50% activity at 4 mg mL−1 of low active FfIBP. These results showed that the protection of proteins from freeze–thaw stress by IBPs is proportional to their IRI activity.